Challenges experienced by clients undergoing assisted reproductive technology in Ghana: An exploratory descriptive study - Kyei, J.M.; Manu, A.; Kotoh, A.M.; Meherali, S.; Ankomah, A. (International Federation of Gynecology and Obstetrics, 2020)
Objective: To explore the experiences of clients accessing assisted reproductive technology (ART) services in selected health facilities in Greater Accra, Ghana. Methods: An exploratory, descriptive, qualitative design using a purposive sampling technique was employed. Overall, 12 women and six men participated in the study. In-depth interviews were conducted using a semi-structured interview guide. The Braun and Clarke (2006) procedure for data analysis was followed. Data collection spanned 9 months (January to October 2017). Results: Five major challenges were identified that were commonly experienced by our participants at every phase of the ART treatment, including the high cost of ART treatment, the long distance to treatment centers, drug treatment challenges, disturbances in daily routine and work, and anxiety about pregnancy outcome. Conclusion: Given the emotional and psychological challenges reported by the participants in the present study, an integration of counseling units in the ART centers is recommended, manned by qualified personnel such as clinical psychologists and counselors to support clients at every stage of the treatment. Also, given the high cost of ART services, as reflected in the participants’ views, it is recommended that private health insurance companies fund some aspect of ART services, such as laboratory investigations and medications.
Research Article
Keywords: Access; Assisted reproductive technology; Experience; Ghana; Infertility; Qualitative study